The compensation and moral damages for false paternity - Castañeda Méndez, Juan Alberto (2024)
This article focuses on the problem of false attribution of paternity and the need for compensation for moral damages in specific cases. Its main objective is to determine whether compensation for moral damages is due to false paternity. For this purpose, a qualitative approach and descriptive design were used, applying interviews to ten lawyers specialized in Family Law. One of the most relevant results was that, when the false attribution of paternity is discovered, there is moral damage, originating an affectation to the right to identity, belief of false filiation, defilement of the duty of fidelity and creation of a civil liability. In this sense, the problem poses not only a legal challenge, but also a palpable violation of fundamental rights, so that financial compensation for the damage should be a priority as a form of reparation for moral damage.